2018
DOI: 10.3906/zoo-1708-44
|View full text |Cite
|
Sign up to set email alerts
|

Benthic invertebrates associated with subfossil cold-water coral frames and hardgrounds in the Albanian deep waters (Adriatic Sea)

Abstract: The fauna collected associated with subfossil Lophelia pertusa and Dendrophyllia cornigera coral samples and hardgrounds from Albanian waters between 190-230 m is discussed. Eighty-three benthic species are recorded: 2 Foraminifera, 22 Porifera, 6 Cnidaria, 25 Mollusca, 14 Annelida, 1 Arthropoda, 12 Bryozoa, and 1 Echinodermata. Seventy-four species are new records for the poorly investigated Albanian deep waters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The interdigitation is, however, not simple as it is between test plates of a number of echinoids (Moss & Meehan, 1967; Smith, 1980), which will separate upon prolonged treatment with bleach. Instead, by its mechanically interlocking trabeculae, the campylogomphosis is similar in morphology to the interconnections of desmas of lithistid sponges (Kelly, 2007; Nasto et al, 2018), the jigsaw puzzle‐like septal sutures of advanced ammonoids (Hoffmann et al, 2018), and cranial sutures of mammals (Seilacher, 1979; White et al, 2021). In these cases, the shapes of extensions between skeletal pieces mechanically and inextricably lock the pieces together even if the joints are further strengthened later in growth by ankylosis, as in mammalian crania.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interdigitation is, however, not simple as it is between test plates of a number of echinoids (Moss & Meehan, 1967; Smith, 1980), which will separate upon prolonged treatment with bleach. Instead, by its mechanically interlocking trabeculae, the campylogomphosis is similar in morphology to the interconnections of desmas of lithistid sponges (Kelly, 2007; Nasto et al, 2018), the jigsaw puzzle‐like septal sutures of advanced ammonoids (Hoffmann et al, 2018), and cranial sutures of mammals (Seilacher, 1979; White et al, 2021). In these cases, the shapes of extensions between skeletal pieces mechanically and inextricably lock the pieces together even if the joints are further strengthened later in growth by ankylosis, as in mammalian crania.…”
Section: Discussionmentioning
confidence: 99%
“…The five categories of suture recognized by Irimura and Fujita (2003) should be examined at higher magnification under the SEM to reveal the relationship among appearance of the suture, degree and locations of ankylosis, and possible phylogenetic relationships. Comparison with the sutures between desmas of lithistid sponges (Kelly, 2007; Nasto et al, 2018), septa of ammonoids (Hoffmann et al, 2018), and cranial plates of mammals (Seilacher, 1979; White et al, 2021) might reveal basic themes in convergence of skeletal features. Finally, sutures between echinoderm ossicles have significantly different biomechanical properties than solid plates (Lawrence, 1987; Moss & Meehan, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…The most studied thanatocoenoses in the basin are those constituted by cold-water corals in the form of reef-like bioherms or unconsolidated rubble (Taviani et al 2011;Enrichetti et al 2023), although others have been investigated, dominated by remains of bivalves, polychaetes, and sponges (Rosso et al 2010;Maldonado et al 2015;Taviani et al 2019), some of which associated to a living counterpart. Various studies also targeted the taxonomic identification of the fauna, both living and dead, associated with these frameworks in order to give a better overview of the paleo-communities (Taviani and Colantoni 1984;Zibrowius and Taviani 2005;Rosso et al 2010;Nasto et al 2018;Taviani et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of subfossil CWC reefs in Albanian waters had long been known by fishermen, yet it was not until recent years that their presence was properly documented (Nasto et al, 2018), quickly followed by the discovery of isolated, yet alive, M. oculata and L. pertusa colonies (Angeletti et al, 2014). While all data regarding its sponge fauna comes from a single sampling of the subfossil reefs (Nasto et al, 2018), the Albanian waters represent a unique CWC site, as it is one of the only known southeastern Adriatic CWC communities, and it has been suggested that it might play a major role on the connectivity of two of the Adriatic and Ionian Sea CWC communities (Chimienti et al, 2019), which, objectively, makes it worthy of inclusion. Finally, the area is also part of the Ionian Sea EBSA area (Gabrie et al, 2012), established in part due to the exceptional presence of CWC in the area.…”
Section: The Albanian Subfossil Reefs (Al)mentioning
confidence: 99%